Development of Phosphorus and Ammonium-Nitrogen Concentration Calibration Curve Using Laboratory Resistivity Method at Alkaline pH Condition - Mohamad Khairuddin, Muhammad Asyraf; WAN MOHAMED @ WAN ABD GHANI, WAN AFNIZAN (Recent Trends in Civil Engineering and Built Environment, 2021)
Phosphorus and ammonium nitrogen are typically an essential part of the living ecosystem, but the amount needs to be at the optimum level. The concentration level can impact the nature of the water and the environment around it. Water resistivity method can be applied in-situ to obtain the resistivity value of the water body. This study was proposed to develop the phosphorus and ammonium nitrogen concentration calibration curve using laboratory resistivity method at pH condition. A laboratory experiment was conducted to obtain the resistivity value of different concentration of phosphorus and ammonium nitrogen at alkaline condition range from 7.8 to 11.0. The resistivity value was obtained using electrical resistivity box and analysed to obtain the calibration curve. The concentration of phosphorus was divided into three ranges which is low range covers from 1 mg/L to 99mg/L, medium range covers from 100 mg/L to 999mg/L and high range covers from 1000 mg/L to 2000 mg/L while the concentrations of ammonium-nitrogen standard are divided into three major groups which is low range covers from 1 mg/L to 99mg/L, medium range covers from 100 mg/L to 999mg/L and high range covers from 1000 mg/L to 5000 mg/L .The results in this lab experiment show that the concentration of the phosphorus and ammonium nitrogen was inversely proportional to the resistivity value. This is because the high number of ions will results in the high conductivity and low resistivity. The calibration curves that have been obtained including R2 value can be used as the references to determinte the water quality by measuring the resistivity in-situ of the water body